2009
DOI: 10.1111/j.1365-3156.2009.02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of childhood vaccination coverage and the impact of maternal HIV status on child vaccination status in rural KwaZulu‐Natal, South Africa*

Abstract: ObjectivesTo analyse coverage of childhood vaccinations in a rural South African population and investigate whether maternal HIV status is associated with children’s vaccination status.Methods2 431 children with complete information, 12–23 months of age at some point during the period January 2005 through December 2006 and resident in the Africa Centre Demographic Surveillance Area at the time of their birth were investigated. We examined the relationship between maternal HIV status and child vaccination statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 49 publications
4
53
2
1
Order By: Relevance
“…However, because these distance differences were relatively small and maps did not identify large pockets of underserved area, it does not appear that distance was a major barrier to enrollment in HIV care. Although other studies have indicated a significant distance-decay effect in health care use with increasing distance for pediatric sick visits, 6 acute infections, 1 pediatric immunizations, 40 infant deliveries, 41 and ART, 42 it is unclear if this holds true for HIV services currently in this adult population and region. Kenya has rapidly decentralized HIV care services to lower level facilities, and although comprehensive HIV care services, including ART, are not available at all healthcare facilities, they are much more available than in prior years.…”
Section: Discussionmentioning
confidence: 98%
“…However, because these distance differences were relatively small and maps did not identify large pockets of underserved area, it does not appear that distance was a major barrier to enrollment in HIV care. Although other studies have indicated a significant distance-decay effect in health care use with increasing distance for pediatric sick visits, 6 acute infections, 1 pediatric immunizations, 40 infant deliveries, 41 and ART, 42 it is unclear if this holds true for HIV services currently in this adult population and region. Kenya has rapidly decentralized HIV care services to lower level facilities, and although comprehensive HIV care services, including ART, are not available at all healthcare facilities, they are much more available than in prior years.…”
Section: Discussionmentioning
confidence: 98%
“…A survey of over 2000 children between the ages of 12 and 23 months in South Africa found maternal HIV status to be a risk factor for decreased immunization coverage for several childhood immunizations, including HBV [53]. …”
Section: Vaccination Coverage and Prevention Of Hbv In Hiv-infected Chimentioning
confidence: 99%
“…Some of these findings are in conformity with an earlier South African study. 18 These findings show that the unemployed status of HIV-infected mothers contributes to their children being incompletely vaccinated. The inability of the unemployed and poorer mothers to source funds for transport to health centres for scheduled vaccinations may be a vital reason for the non-uptake of the vaccines.…”
Section: Discussionmentioning
confidence: 90%